Association between Hypertensive Disorders in Pregnancy and Postpartum Mental Health - Sarosh, Muntiha; Ghafoor, Faiza; Shakoor, Shumaila (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the relation between prevalence of Postpartum Depression and varying degrees of severity of Hypertensive Disorders in Pregnancy. Study design: A cross sectional study . Place & duration of study: Department of Obs. & Gynae, Avicenna Hospital, Lahore from June 2020 to December 2021. Methodology: A total of 220 women with and without hypertensive disorders of pregnancy (110 in each group) delivered during this period were enrolled in the study. A survey in the post partum period from second to sixth week postpartum was carried out. It was done according to the Edinburgh Postnatal Depression Scale (EPDS) to assess the effect of severity of Hypertensive disorders of pregnancy to develop new-onset postpartum depression. Results: 220 women were enrolled in the study. Among them Forty five women showed sign and symptoms of post partum depression. On the other hand 175 had no manifestation of depression according to the scale. The prevalence of PPD was 27 % (30/110) in women with hypertensive disorders, being twice the value in normotensive subjects (13.6%). The risk of Post partum depression surged with the aggressiveness of hypertensive disease in pregnancy. Conclusion: Preeclampsia has an independent association with Post partum depression. The risk of Post partum depressive disorder seemed to increase with the rising severity of hypertension in pregnancy. Therefore support and additional preventive strategies should be planned for women with Preeclampsia to reduce the likelihood of Post partum deterioration of mental health.